2016
DOI: 10.21577/1984-6835.20160130
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Thermal Stability of Two Peroxidases from Pithecellobium dulce (Roxb.) Benth. Aril

Abstract: Resumo: Duas formas de peroxidase (POX), denominadas PdPI e PdPII, foram parcialmente purificadas de arilos de Pithecellobium dulce, utilizando precipitação com sulfato de amônio e cromatografia de troca iônica. O zimograma das proteínas obtidas após precipitação com sulfato de amônio na faixa de 60 a 90% de saturação (fração F6090), mostrou duas bandas com atividade peroxidásica. Na coluna de celulose DE-52, a atividade peroxidásica foi detectada nos picos não adsorvido (PdPI) e adsorvido (PdPII) eluído com N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The optimum pH for the activity of the enzyme was determined using sodium acetate buffer solution of (0.2 M) with pH values ranging from 3.5-5.5, sodium phosphate buffer solution with pH value ranging between 6.0-7.5, and Tris-HCL buffer solution with a pH value (8)(9) to prepare the substrate solution. The reaction carried out by incubating the substrate with enzyme for each pH (3.5-9.0) in test tubes for 15 minutes in a water bath at 37 ° C, then it was cooled directly in an ice bath to stop the enzymatic reaction and the enzymatic activity determined as explained previously and then the relationship between the enzyme activity and the pH values is plotted.…”
Section: Determination Of the Optimum Ph For The Peroxidase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum pH for the activity of the enzyme was determined using sodium acetate buffer solution of (0.2 M) with pH values ranging from 3.5-5.5, sodium phosphate buffer solution with pH value ranging between 6.0-7.5, and Tris-HCL buffer solution with a pH value (8)(9) to prepare the substrate solution. The reaction carried out by incubating the substrate with enzyme for each pH (3.5-9.0) in test tubes for 15 minutes in a water bath at 37 ° C, then it was cooled directly in an ice bath to stop the enzymatic reaction and the enzymatic activity determined as explained previously and then the relationship between the enzyme activity and the pH values is plotted.…”
Section: Determination Of the Optimum Ph For The Peroxidase Activitymentioning
confidence: 99%
“…In addition, peroxidase can modify the gluten network by cross-linking the gluten proteins or by introducing arabinoxylans to gluten proteins [6,7]. Research on peroxidase enzymes from a wide variety of plants suggested that the enzyme's physical and kinetic properties, as well as its substrate choice, may vary greatly, even within a single source [8,9]. Furthermore, it is well believed that peroxidase activity and related enzyme patterns fluctuate with changes in plant development.…”
Section: Introductionmentioning
confidence: 99%